Assay strategies for identification of therapeutic leads that target protein trafficking. (August 2015) - Conn, P. Michael; Spicer, Timothy P.; Scampavia, Louis; Janovick, Jo Ann
Highlights This article describes a novel approach for drug development by targeting the trafficking of receptor and enzyme proteins. Strategies are described for the development of high throughput assays for the identification of this class of drugs.